All-round Development and Comprehensive Assessment Bridging the Gap - Dey, Tulika; Ghildyal, Prachi (JOURNAL OF INDIAN EDUCATION, 2021)
This paper puts forth ideas about holistic assessment for all-round development of children. It states that comprehensive assessment has been started without ensuring opportunities for all-round development. It begins with the basic question of why should we assess and finds that the goal of assessment is to facilitate all-round development of the learner. Continuous and Comprehensive Evaluation (CCE) was implemented without emphasising the need and methods of all-round development. This effectively led to the assessment of abstract qualities and aspects of a student’s personality without having made any prior efforts ever to develop those. Elaborating on the understanding of all-round development, the paper then discusses some strategies for assessment for all-round development. It places more emphasis on assessment of the affective domain and highlights some fallouts of a widespread misunderstanding of assessment.